Rapid progression from complete molar pregnancy to post-molar gestational trophoblastic neoplasia: a rare case report and literature review - Qian, Jing; Gracious, Kaoma; Sun, Liping (Frontiers in Oncology, 2023)
Post-molar gestational trophoblastic neoplasia (pGTN) develops in about 15% to 20% of complete hydatidiform mole (CMH). Commonly, pGTN is diagnosed based on hCG monitoring following the molar evacuation. To date, no detailed information is available on how fast can pGTN develop from CHM. However, the concurrence of CHM and pGTN is extremely rare.A 29-year-old woman presented to the gynecology department with irregular vaginal bleeding and an elevated hCG serum level. Both ultrasound and MRI showed heterogeneous mass in uterine cavity and myometrium. Suction evacuation was performed and histologic examination of the evacuated specimen confirmed complete hydatidiform mole. Repeated ultrasound showed significant enlargement of the myometrium mass one week after the evacuation. pGTN with prognostic score of 4 was then diagnosed and multiagent chemotherapy regimen implemented with a good prognosis.In rare cases, CMH can rapidly progress into pGTN. Imaging in combination with hCG surveillance seems to play a vital role guiding timely diagnosis and treatment in the specific condition. Low-risk gestational trophoblastic neoplasia (GTN) should be managed stratified according to the individual situation.